The Effect of Lecturing Technique on the Students’ Reading Achievement - Putri Arnita Harahap; Azhary Tambusai; Ahmad Laut Hasibuan (PT Inovasi Pratama Internasional, 2022)
The objective of the research was to improve the students’ reading achievement of grade X students at SMKN 1 Beringin academic year 2018-2019 by using the lecturing technique. The researcher used the experimental research. The population of the research was grade of students X TKJ1 and X TKJ2, and two classes were chosen as sample of the research in which there were 32 students for experimental class, and 32 students for control group. The actions implemented in this research were using lecturing technique, giving more explanation in English, making use of the LCD projector optimally, and providing activities that enabled the students to improve reading achievement. The research results of the resesarch showed that the use of lecturing technique in the English teaching and learning process was effective to improve the students’ reading achievement. There was an increase in the means score from 8.43 in pre-test to 25.31 in the post-test. There were some good improvements in some aspects such as their familiarity in reading descriptive texts in English. Also, they become actively participating in discussions during the teaching and learning process. They were more aware of mistakes due to correction from other students. In addition, this technique successfully attracted the attention of students. In short, they understood comprehensively the purpose of the text that had been given.